اختلاف مصطلاحات الوقف بين العلماء وموازنته على رأي الجمهور: The Differences Among Scholars in Waqf (Pause) Terminologies and the Evaluation of Majority Scholars - Ahmad, Abdul Muhaimin; Sabri Mohamad; Haziyah Husin (Maʿālim al-Qurʾān wa al-Sunnah, 2017)
The "ilmu al waqf wal ibtida" has received great attention from Muslim scholars - past and present - so they have written many works on different approaches to it. Some of them wrote and took care of the ahkam or rules of the waqf and ibtida with the head and middle verses of the Qur’an separately. And some of them made it a chapter for their books, and explained the rules of waqf and ibtida and their types, with examples of each of those rules and types. Those who reflect on these books find out that they were not agreed on the same terms in the waqf and ibtida and commencement, but for each writer have terms that he reliable. may be The terminology is the same but the purposes are different, while others may reflect this. These various terms may lead to confusion in understanding the ahkam of waqf and ibtida for the verse, especially for the initiators of these books, so they mistook the ahkm of waqf and ibtida for the verses. This study attempted to raise this terminological complexity between these books, by describing what is meant by each of the terms waqf and ibtida used in books of waqf and ibtida, and then compare and measure them on the scale of the divisions of the majority of scholars of this field. In order to achieve these goals, the study chose some of the basic sources in this field, namely "idahul waqf wal ibtida" by Anbari, and al katu wa al iitinaf by nuhas, and Manar Al Huda fi bayan al waqf wa al- ibtida by al-Ashmuni to serve as a model for this study. One of the important results of this study is that some of these terms are agreed in both terms and purposes together, just as others are agreed in terms, but its purposes are different. The study also discovered that some of these terms are intertwined with each other.